Tuning reactivity and mechanism in oxidation reactions by mononuclear nonheme iron(IV)-oxo complexes - Nam, Wonwoo; Lee, Yong-Min; Fukuzumi, Shunichi (Accounts of chemical research, 2014)
Mononuclear nonheme iron enzymes generate high-valent iron(IV)-oxo intermediates that effect metabolically important oxidative transformations in the catalytic cycle of dioxygen activation. In 2003, researchers first spectroscopically characterized a mononuclear nonheme iron(IV)-oxo intermediate in the reaction of taurine: α-ketogultarate dioxygenase (TauD). This nonheme iron enzyme with an iron active center was coordinated to a 2-His-1- carboxylate facial triad motif. In the same year, researchers obtained the first crystal structure of a mononuclear nonheme iron(IV)-oxo complex bearing a macrocyclic supporting ligand, [(TMC)Fe(IV)(O)](2+) (TMC = 1,4,8,11-tetramethyl-1,4,8,11-tetraazacyclotetradecene), in studies that mimicked the biological enzymes. With these breakthrough results, many other studies have examined mononuclear nonheme iron(IV)-oxo intermediates trapped in enzymatic reactions or synthesized in biomimetic reactions. Over the past decade, researchers in the fields of biological, bioinorganic, and oxidation chemistry have extensively investigated the structure, spectroscopy, and reactivity of nonheme iron(IV)-oxo species, leading to a wealth of information from these enzymatic and biomimetic studies. This Account summarizes the reactivity and mechanisms of synthetic mononuclear nonheme iron(IV)-oxo complexes in oxidation reactions and examines factors that modulate their reactivities and change their reaction mechanisms. We focus on several reactions including the oxidation of organic and inorganic compounds, electron transfer, and oxygen atom exchange with water by synthetic mononuclear nonheme iron(IV)-oxo complexes. In addition, we recently observed that the C-H bond activation by nonheme iron(IV)-oxo and other nonheme metal(IV)-oxo complexes does not follow the H-atom abstraction/oxygen-rebound mechanism, which has been well-established in heme systems. The structural and electronic effects of supporting ligands on the oxidizing power of iron(IV)-oxo complexes are significant in these reactions. However, the difference in spin states between nonheme iron(IV)-oxo complexes with an octahedral geometry (with an S = 1 intermediate-spin state) or a trigonal bipyramidal (TBP) geometry (with an S = 2 high-spin state) does not lead to a significant change in reactivity in biomimetic systems. Thus, the importance of the high-spin state of iron(IV)-oxo species in nonheme iron enzymes remains unexplained. We also discuss how the axial and equatorial ligands and binding of redox-inactive metal ions and protons to the iron-oxo moiety influence the reactivities of the nonheme iron(IV)-oxo complexes. We emphasize how these changes can enhance the oxidizing power of nonheme metal(IV)-oxo complexes in oxygen atom transfer and electron-transfer reactions remarkably. This Account demonstrates great advancements in the understanding of the chemistry of mononuclear nonheme iron(IV)-oxo intermediates within the last 10 years.